HUBUNGAN PENGETAHUAN DAN PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN - Maya Safitri; Rahmawati Dewi; Yanti L (Universitas Harapan Bangsa Purwokerto, 2012)
The efforts to increase breastfeeding (ASI) contribute greatly to decrease infantmortality and declining prevalence of malnutrition among children under five. With theattainment of breastfeeding is still far below the national target, a sign that awareness of themothers in breastfeeding still need ditingkatkan.Cakupan exclusive breastfeeding in Banyumas56.2% is still below the target of achieving exclusive breastfeeding in Indonesia by 80%. Basedon the results of a survey conducted in Puskesmas North Purwokerto 1 data obtained ASI lowestcoverage in Sub Purwanegara by 45%. Determine the relationship of mother's knowledge and work with exclusivebreastfeeding in infants aged 0-6 months in Sub Purwanegara District of North Purwokerto,Banyumas regency in 2011. This study is an analytic study with a correlation study. with cross sectional approach.The sample used is total sampling, samples of this study are mothers with babies aged 0-6months. Samples in this study 49 respondents. Instrument in this study was a questionnaire withdata analysis using chi-square. From the results, there is a relationship between knowledge of mothers with exclusivebreastfeeding is largely exclusive breastfeeding mother's knowledge about enough of (44.9%).There is no employment relationship with Exclusive breastfeeding is mostly mothers work asmuch (69.4%), most respondents did not provide exclusive breastfeeding to their babies as much(77.6%). There is a relationship with the mother's knowledge exclusive breastfeeding and noemployment relationship with exclusive breastfeeding. Keywords: Awareness, Employment, Exclusive Breastfeeding